Efficacy of Calcium Phosphate Composite Bone Graft in Treatment of Periodontal Intrabony Defects: Clinico-Radiographic Study - Bilal Haider Shirazi, Syeda Sahar Ali, Muhammad Salman Aminwala, Shaista Zafar, Aleezah Ali, Syed Ahmed Arbaaz, Sabeen Fazal (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The loss of alveolar bone support is the main symptoms of the destructive periodontal disease. Periodontitis leads to formation of the interbony defects. For resolution of the infection, the elimination of IBD is highly needed. For the filing of the IBD and regeneration of the bone in the periodontal therapy, different bone grafts are used. Objective: The study aimed to evaluate the efficacy of calcium phosphate composite bone graft in patients suffering from periodontal intrabony problems. Study Design: It is a randomized and interventional study conducted at Multan Medical & Dental College, Multan and DOW University of Health Sciences, Karachi for the duration of six months from December 2021 to May 2022. Material and Methods: The study was conducted on 16 patients that fulfilled the inclusion criteria. All the patients completed the follow-up. The radiographic parameters were also evaluated. The baseline data from six months and three months was analyzed and data was plotted. Results: It was found that the primary closure was carried out for all the patients. There was no statistical significance found between the groups related to depth of the defect and the walls number groups before operation. There was a prominent reduction in plague concentration and gingival index. In case of test group there was a greater statistical reduction in the test group as compared to the control. The recession of gingival parameter was seen in both the groups. There was no statistical difference observed here. Conclusion This study helps to provide significant results and evidence that the easy graft crystal can be used for the treatment of periodontal intrabony issues. Keywords: Intrabony defects and calcium phosphate composite bone graft